Enhanced FM0 decoder for UHF passive RFID readers using duty cycle estimations - Baustista, N. Fernando B. (College of Engineering, University of the Philippines Diliman, 2011)
In this thesis, we present a novel FMO decoding techniques for EPC Class 1 Generation 2 (C1 G2)UHF RFID readers. The proposed decoder overcomes the limitations of current implementations, which focus on correlation based decoding and require complex synchronization schemes. New rectangular wave symbols are derived from the FMO stream and mapped to corresponding bit sequences using duty cycle estimations. Since the duty cycle approximated is independent of the received data rate, the proposed decoder is unaffected by the large + / - 22% data rate deviation specified by the EPC C1 G2 protocol and can decode the whole data rate range of 40kHz to 640 kHz without changing the decoder structure. Furthermore, the specific sequencing of the rectangular wave symbols allows for early bit error detection prior to CRC computation. The duty cycle based decoder is prototyped on a Xilinx Virtex 5 FPGA and subsequent FPGA utilization data are presented and compared with a correlation-based scheme. Experimental results show that at 10-3 BER level, the proposed decoder achieves 1 dB and 2 dB SNR gains over a practical correlation-based decoder at 38 and 625 samples per symbol, respectively.